Building local ecosystems for social innovation: A methodological framework - OECD Centre for Entrepreneurship, SMEs, Regions and Cities (CFE) (OECD Local Employment and Economic Development (LEED) Papers, 2021)
Social innovations have proven to be valuable in identifying, designing and implementing new solutions to social and environmental problems. The recent COVID-19 outbreak has put a spotlight on the potential of social innovation as a resilience mechanism, including for local development. This paper presents a preliminary framework for analysing social innovation ecosystems at the local level. It can help policy makers to better understand the different concepts around social innovation, and to develop policies to support social innovation and its implementation. The first section considers the features of social innovation and the benefits it can bring. The second section provides an analytical framework for social innovation at the local level. The final section sets a number of guidelines that support the implementation of social innovation ecosystems at local level, including examples of specific policy instruments.
Keywords: Innovation sociale; Mesures; Réservé UdeM; Social entrepreneurship; local ecosystem; Économie sociale